2013
DOI: 10.1055/s-0033-1338555
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Water-Soluble Vinyl Selenides and Their High Glutathione Peroxidase (GPx)-Like Antioxidant Activity

Abstract: A convenient procedure for the synthesis of novel bis-(1-hydroxymethyl-2-halo-3-hydroxy-1-propylene) selenides has been developed. On oxidation these compounds form novel seleno-spiro compounds and their glutathione peroxidase mimetic activity has been studied. They promote the hydrogen peroxide oxidation of phenylmethanethiol to the corresponding disulfide via a catalytic cycle.Key words: alkynes, selenium, oxidation, spiro compounds, diols Glutathione peroxidase (GPx) is a selenoenzyme that protects cells by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…Braverman et al . investigated the GPx‐like activity of the water‐soluble unsaturated spirodioxyselenuranes 47 and its precursor selenides 46 , which exhibited higher activity than ebselen.…”
Section: Spirodioxyselenuranessupporting
confidence: 55%
“…Braverman et al . investigated the GPx‐like activity of the water‐soluble unsaturated spirodioxyselenuranes 47 and its precursor selenides 46 , which exhibited higher activity than ebselen.…”
Section: Spirodioxyselenuranessupporting
confidence: 55%
“…The interactions selenium(VI) species form with oxygen reflect more conventional Lewis acid-Lewis base interactions. There are 18 selenium(IV) species, 33 – 50 [100] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] , and five selenium(VI) species, 51 – 55 [116] , [117] , [118] , [119] , forming Se … O contacts leading to zero-dimensional aggregates, with the chemical diagrams for the interacting species in these shown in Fig. 4 .…”
Section: Zero-dimensional Assembles Mediated By Se … mentioning
confidence: 99%
“…The majority of the selenium(IV) compounds form centrosymmetric dimers, indeed 14 of the 18 crystals feature this motif, and each of these is constructed about a four-membered { … Se–O} 2 synthon. Compounds 33 [102] , 34 [103] , 35 – 37 [104] conform to the general formula R(R′)Se O. The dimeric aggregate for 34 , being representative for this series, is shown in Fig.…”
Section: Zero-dimensional Assembles Mediated By Se … mentioning
confidence: 99%
“…It should be noted that the syntheses of substituted bis(1‐chloro‐1‐propen‐2‐yl) selenoxides remain solitary in the literature. For example, it was reported that the oxidation of adducts of propargylic alcohol and selenium dichloride proceeded via the intermediate formation of unstable bis(1‐chloro‐1‐propen‐2‐yl)selenoxides, which further cyclized across the hydroxyl groups to give selenospiro compounds. Similar selenoxides were prepared by hydrolysis of bis(1‐chloro‐1‐propen‐2‐yl)selenium dichlorides, adducts of propargylic alcohols and selenium tetrachloride, with aqueous solution of sodium hydrocarbonate .…”
Section: Resultsmentioning
confidence: 76%